Linear Regression Analysis on the Determinants of Hypertension Prevention Behavior - Nurjannah Nurjannah; Setyo Sri Rahardjo; Rossi Sanusi (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Hypertension is a risk factor for cardiovascular events and the highest contributor to death in the world, including Indonesia. 90.08% of health centers in DI Yogyakarta have implemented integrated non-communicable disease (NCD) control. However, the incidence of NCD including hypertension is still the highest disease seen from the top 10 diseases in Yogyakarta. This study aimed to examine the determinants of hypertension preventive behavior.Subjects and Method: This was a cross sectional study conducted in Bantul, Yogyakarta, from February to March 2019. A total of 200 study subjects was selected by simple random sampling. The dependent variable was hypertension preventive behavior. The independent variables were self-efficacy, knowledge, family support, gender, age, and health personnel support. The data were collected by questionnaire and analyzed by a multilevel linear regression.Results: Self-efficacy (b= 0.09; 95% CI= 0.03 to 0.15; p= 0.003, knowledge (b= 0.25; 95% CI= 0.08 to 0.43; p= 0.004), family support (b= 0.64; 95% CI= 0.34 to 0.93; p <0.001), and health personnel support (b= 0.26; 95% CI= 0.08 to 0.44; p= 0.008) increased hypertension preventive behavior. Gender (b= 0.65; 95% CI= -0.79 to 2.10; p= 0.372) and age (b= 0.01; 95% CI= -0.03 to 0.03; p= 0.911) were associated with hypertension preventive behavior but it was statistically non-significant.Conclusion: Self-efficacy, knowledge, family support, and health personnel support increase hypertension preventive behavior. Gender and age were associated with hypertension preventive behavior but it was statistically non-significant.Keywords: hypertension preventive behavior, self-efficacy, health personnel support Correspondence: Nurjannah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nurjannah9420@gmail.com. Mobile: +6285293622882.Journal of Health Promotion and Behavior (2019), 4(1): 22-31https://doi.org/10.26911/thejhpb.2019.04.01.03